Implikasi Doktrin Kepentingan Yang Sewajarnya Pada Media Streaming Online Youtube.com - Panji Rystho Ramadhan; Umar Al-Haddad; Asrori S. Karni (JOURNAL of LEGAL RESEARCH, 2019)
Abstract. Copyright Law is a rule that enables the exclusivity of the creator to manipulate their invention for their own good. Fair use doctrine is enabling other people to use the content/art who belong to other people without their permission for studied, research and non-profit purposes. The object of the copyright law is written on the Law of Number 28 the year 2014 about Copyright. This research is using qualitative and Normative empiric approaches. The result of this research showed that Youtube unwritten gave permission to peoples used other creations as long it is for criticism, comment, play gaming, song cover as long it makes a new source of art and creation as long the real creator is okay with it.Keywords; Intellectual Property, Fair Use Doctrine, Youtube